Self-compacting concrete beams reinforced with steel fiber under flexural loads: A ductility index evaluation - Odaa, Sief aldeen; Hason, Mahir M.; Sharba, Amjad Ali K. (Materials today : proceedings, 2021)
Although the ductility index of the reinforced concrete element has been the subject of many research objectives and critical analysis recently, scare consideration is carried out to measure the ductility of reinforced self-compacting concrete (SCC) enhanced with steel fiber. Hence, the current study aims to evaluate the ductility, in terms of energy absorption, of reinforced steel fibrous self-compacting concrete beams subjected to experimental flexural force. Twelve reinforced SCC beams experimented under flexural loads including pair groups of six beams (with and without steel fibers). Minimum and maximum steel ratio (ρmin and ρmax) and three grades of concrete (G20, G50, and G60) are used in this study. Load-displacement curves (P-Δ) are used as a tool to measure the ductility Energy index (μE) of the tested SCC beams using Spadea et al (1997) technique. The result shows that the flexural stiffness of the fibrous SCC beam specimens is improved to overcome beam deformation and consequently constrained cracking. The results reveal also that the increase of fibrous material to SCC is extremely efficient. In terms of increasing energy dissipation, flexural capacity, and ductility index (μE). Besides, the flexural strength grows with increasing steel fiber percentage, steel reinforcement ratio, and concrete compressive strength.